Testing corrosion inhibiting, engine coolant concentrate ('antifreeze'). Methods of test for corrosion inhibition performance. Test for corrosion of cast aluminium alloys under heat-transfer conditions Part 2.6, (1st May 1992) - British Standards Institution,
No abstract available